A study on the application of section 135 of Customs Act 1967 in preventing smuggling offences / Nik Asilah Aziz, Syaqif Aiman Sharom and Yasmin Natasha Yusri Kamaruzaman - Aziz, Nik Asilah; Sharom, Syaqif Aiman; Yusri Kamaruzaman, Yasmin Natasha (2011)
This research analyses on the application of the law in Malaysia to control the existing problems regarding to smuggling offences and the need of amendment of section 135 of custom act to ensure that the amendment of this law will help in reducing smuggling offences. After identifying the problems that exists under this scope of study, recommendations were made with the intention to improve certain aspects regarding the enforcement of the law and not the law per se. The first chapter basically explains the essence and structures of the research. The second chapter is on the Malaysian authorities, smuggling factors in Malaysia and other Asian countries and the application of Section 135(1) of the Customs Act 1967 which is essential in controlling the smuggling activities. Chapter three provides the comparison made on the Law with regard to smuggling in Malaysia, Singapore and Brunei. The fourth chapter touches on the results and findings obtained by the researches based on an interview and a survey made on a number of respondents. The final chapter concludes the research by providing a conclusion pertaining to this title and some recommendations were made for the purpose of improving the enforcement of Section 135(1) of the Customs Act 1967 by the rightful authorities and to guarantee the efficacy of the law on putting an end to smuggling activities.